The influence of 8 weeks of aerobic, strength and mixed exercises on the performance of short-term memory of women - Delir, A.; Mohammadi, F. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The purpose of this study was to investigate the effect of 8 weeks of aerobic, strength and mixed exercise on short-term memory performance of women. It is a quasi-experimental study accomplished by a pre/posttest plan with three experimental groups and one control group. A total of 60 female volunteers were selected, randomly, allocated to four groups including: aerobic group, strength group, aerobic-strength group and control group. All the groups performed their training protocols. Measurement of short-term memory performance was done using memory span test in two steps pre and post of exercise sessions. Data was analyzed using dependent t-test and covariance test. Least significance difference (LSD) test was used to compare groups. The results suggest that 8 weeks of aerobic (p=0.001), strength (p=0.001) and strength-aerobic (0.029) exercise increases memory performance. The results of covariance test showed that 8 weeks of aerobic, strength and aerobic-strength exercise affect short-term memory of women differently. Also, the results of mean comparison test suggest that there is a significant difference between control, aerobic-strength and strength groups (p<0.05). Clinically speaking, these findings prove the importance of aerobic, strength, and aerobic-strength exercise in preserving and improving memory performance.